Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376284
|View full text |Cite
|
Sign up to set email alerts
|

Designing for Employee Voice

Abstract: We then operationalised these qualities as a set of design goals-Assured Anonymity, Constructive Moderation, Adequate Slowness and Controlled Access-in the design and development of a secure anonymous employee voice system. Our novel take on the Enterprise Social Network aims to foster good citizenship whilst also promoting frank yet constructive discussion. We reflect on a two-week deployment of our system, the diverse range of candid discussions that emerged around important workplace issues and the potentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…In this context, this work shares some interest with previous studies that have investigated the use of computer-mediated communication in specifc situations, such as workplace communication [1,31].…”
Section: Use Of Computer-mediated Communication In Specifc Situationsmentioning
confidence: 76%
See 2 more Smart Citations
“…In this context, this work shares some interest with previous studies that have investigated the use of computer-mediated communication in specifc situations, such as workplace communication [1,31].…”
Section: Use Of Computer-mediated Communication In Specifc Situationsmentioning
confidence: 76%
“…Subsequently, I manually crawled the websites and social media accounts of each group and checked whether the group had released some announcement about meet-and-greet events between February 26 1 and August 25, 2020. As a result, I collected the announcements of 53 idol groups, which had over 700 members in total.…”
Section: Qualitative Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological safety may be provided either through an organizational climate where voice is encouraged and supported (Duan et al, 2022;X. Liu et al, 2022;Morrison, 2014) or through voice/communication mechanisms' features that may provide privacy/anonymity when voicing (Abdulgalimov et al, 2020;Mao & DeAndrea, 2019). Contrary to what Knoll et al (2022) posit regarding digital media lowering employees' perceived safety to express challenging voice, we argue that where anonymity is provided, SM could enhance employees' perceived safety to voice.…”
Section: Perceived Safety To Voice Versus Low Privacymentioning
confidence: 70%
“…Voice on SM may also be difficult to action, resulting in potential delays to response. In their study of designing effective SM for voice, Abdulgalimov et al (2020) found anonymity to be a double-edged sword; while it provides employees confidence to voice their concerns, anonymous voice can be difficult for management to action. Concerns regarding authenticity have been raised whereby information, suggestions, ideas or concerns expressed anonymously have built tensions between credibility of information and the need to express oneself openly (Scott et al, 2011).…”
Section: Access To Key Decision-makers Versus Low Target Response To ...mentioning
confidence: 99%